Nigerian Languages, Literatures, Culture and Reforms - Ndimele, Ozo-mekuri (Festschrift series (Port Harcourt, Nigeria), 2016)
The papers in this volume were selected from the Silver Jubilee edition of the Annual Conference of the Linguistic Association of Nigerian (LAN) which was held at the Nigerian Educational Research and Development Council (NERDC), Abuja, Nigeria. The Silver Jubilee edition is dedicated to the father of Nigerian Linguistics, Professor Emeritus Ayo Bamgbose. Professor Emeritus Bamgbose was the first indigenous Professor of Linguistics in Nigeria, and the first black African to teach linguistics in any known university south of the Sahara. He was there from the very beginning, and together with co-operation of people such as the late Professor Kay Williamson, he nurtured Nigerian linguistics. He is not just a foremost Nigerian linguist, but also a most famous, respected, celebrated, distinguished, and cherished African linguist of all times. To be candid, Nigerian linguistics is synonymous with Professor Emeritus Bamgbose. In 58 well-written chapters by experts in their fields, the book covers aspects of Nigerian languages, linguistics, literatures and culture. The papers have not been categorized into sections; rather they flow, hence there is some overlapping in the arrangement. The book is an essential resource for all who are interested to learn about current trends in the study of languages, linguistics and related subject-matters in Nigeria.